HAK ANAK DAN KELUARGA SEJAHTERA DALAM WACANA YURIDIS - Sri Prastyowati (Sosio Informa, 2004)
Child Rights and Family Welfare in the Judicial Context.In the process of social transformation from agricultural society to industrial society, meansand values have been changing that affectly family function. Modernization encouraged family members to engage outside home that has been decreasing the family care giving to children become more selected. This article tries to analyze the rights of children from their parents m the context of changing family in Indonesia.